Pemanfaatan Endapan Lumpur Hasil Sedimentasi Untuk Pembuatan Produk Batu Bata Interlock Bernilai Ekonomis - Saputro, Dani Nugroho; Susanto, Hery Awan; Hermanto, Nor Intang Setyo; Rahmawati, Eni; Januardi, Redityo (Madani : Indonesian Journal of Civil Society, 2025)
The results of the dredged sludge deposits due to sedimentation of the Jenderal Besar Soedirman reservoir are quite large and have the potential to be utilized. The problem that arises is that the sedimentation results are not immediately removed, it will disrupt several sectors, especially the power generation sector (PLTA). From this problem, an alternative emerged to utilize the dredged sludge deposits due to sedimentation into bricks that have economic value. The utilization of sludge deposits into bricks aims to reduce excessive sedimentation in the JB Soedirman sludge reservoir. If the sludge deposits are utilized properly, one of which is as a material for making Interlock bricks, it will create economic value for the community, especially in Banjarnegara, Purbalingga dan Banyumas Regency, there are many business sectors engaged in making bricks. The method used in this community service is observation and demonstration, the first is to conduct further observation studies on the nature of the dredged sludge deposits by conducting laboratory tests, from the results of the tests, information and education are provided to the business community on how to utilize sludge deposits into bricks with the right composition and high quality. It is expected that with this Community Service activity, it can overcome the problems that arise and improve the economy of brick entrepreneurs around the reservoir without having to mine or buy raw materials for production. Brick entrepreneurs are very enthusiastic about unbaked interlocking bricks, by making innovations in the brick business.